Peningkatan Hasil Belajar IPA Melalui Model Pembelajaran Think Pair Share (TPS) Berbantuan Media Telepon Kaleng Sederhana - Rochmayanti, Sri (Prosiding University Research Colloquium, 2021)
This study aimed to determine the improvement of in science learning outcomes through the Think Pair Share model using Canned Telephone Media for Grade IV students of SDN Tegalrejo in the academic year of 2019/2020. The study was classroom action research conducted in two cycles. Each cycle consisted of planning, acting, observing, and reflecting. The subjects were 30 fourth grade students at SDN Tegalrejo. The data collection results were analysed using the test. The test results were analysed by descriptive-quantitative technique. It showed that there was an improvement in learning outcomes from the Pre- cycle by an average of 58.6 with a percentage of the MMC value of 40%. The Cycle I was 77.2 by a percentage of the MMC value of 70% and Cycle II was 89.7 by a percentage of the MMC value of 96.6%. The results indicated that science learning using the Think Pair Share model using Telephone Cans Media can improve the learning outcomes of fourth grade students of SDN Tegalrejo in the academic year of 2019/2020.